Analisis Perbandingan Protein Hewani dan Nabati dalam Memenuhi Asupan Protein Harian - Zahira Farini Hasbani; Dian Isti Angraini; Terza Afika Happy; Reni Zuraida (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Protein is an essential macronutrient that plays a crucial role in growth, tissue repair, enzyme and hormone synthesis, and in supporting metabolic and immune functions. This study aims to comparatively analyze the effectiveness of animal and plant proteins in meeting daily protein requirements. The method used is a literature review by examining 19 scientific journal articles and official reports that discuss the role of protein, amino acid quality, bioavailability, and the long‑term health impacts of each protein source. The analysis shows that animal protein has high biological quality, contains all essential amino acids, and is easily absorbed by the body, making it effective in supporting growth, muscle mass development, and metabolic functions. Meanwhile, plant protein, although some sources lack certain essential amino acids, offers long‑term health benefits, is low in cholesterol, high in fiber, and environmentally friendly. Combining various plant protein sources can ensure the intake of all essential amino acids. In conclusion, the optimal strategy for meeting daily protein needs is to combine animal and plant proteins, thereby supporting high nutritional quality, optimal growth and body function, as well as long‑term health and environmental sustainability. These findings provide an important reference for the general public, nutritionists, and policymakers in designing healthy and balanced dietary patterns.